PERANAN AUDIT INTERNAL TERHADAP KEPATUHAN STANDAR OPERASIONAL PROSEDUR (SOP) PADA PT X - Wulandari, Tri; Fidiana, Fidiana (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis researchâs goal is for knowing the role of internal audit to Standard Operating Procedure (SOP) in PT X, checking employee performance to reach an effective and efficient performance it is also to see the result of employee performance which its possibility doing standard operating procedure deviation had been done by the parties of internal company.This reseach is a descriptive research, done in PT X. The subject is the head of department (Internal Audit, Accounting, Financial and Credit Analyst). The object is the role of Internal Audit to standard operating procedure obeisance. The datas collecting techniques are interview and documentation. Research analyze technique is qualitatif analyze by using primary and secondary data. The result of this research shows that the role of internal audit to standar operasional procedure obeisance of PT X is very important. It can be seen by employee performance already good enaugh in doing their duties and function given by the company. In other hand at a new education year, happen some cancelled jobs on such kind of parts as maintenance and administration. It is showed by audit result gound that shows some system and procedure deviation caused by the lack of company documents checking.Keywords : Internal Audit, Standard Operating Procedure, Performance